How 10 global cities take on homelessness : innovations that work - Gibbs, Linda, 1959-; Bainbridge, Jay, 1963-; Rosenblatt, Muzzy, 1965-; Mammo, Tamiru, 1972- (University of California Press, 2021)
"Here an academic, a Principal and Manager at Bloomberg Associates, and President of Bowery Residents Committee take on perhaps the most formidable issue facing metropolises today: the large numbers of homeless residents within cities. Ten Global Cities will provide a first-hand account of the challenges of homelessness and how cities have used innovation and local political coordination to take them on. Most importantly, it shares lessons from ten cities globally--Bogota, Mexico City, Los Angeles, Houston, Nashville, New York City, Baltimore, Edmonton, Paris, and Athens--and draws the common themes and strategies that have worked to overcome street homelessness. The authors have been involved in these cities through their work at Bloomberg Associates (as staff and consultants) and bring an interesting array of government, non-profit, and academic perspectives to analyze the efforts underway. From these authors' perspective, homelessness is not an insurmountable social condition, and their examples show that cities can lead the charge for better outcomes. Intended readers include municipal, regional, and national policy makers and managers, non-profit service providers, and community advocates and citizens interested in collaborating for real change. Policy students in public administration and social work would also benefit from such an up-to-date account of best practices on the homelessness front"--